From 'a woman's place is in her union' to 'strong unions need women': changing gender discourses, policies and realities in the union movement. (2nd October 2017) - Kirton, Gill
ABSTRACT: This article draws on research that I along with others have conducted in various countries and regions of the world, which highlights the changed and evolving gender context within the union movement. From the late 1970s onwards, the campaign for women's equality and gender democracy within unions gathered pace under the influence of second wave feminism. New discourses were espoused and new practices adopted towards these goals, and some countries, some unions have achieved greater success than have others. The article considers the contemporary landscape, continuity and change in the global union movement's unfinished gender democracy project.